Dielectric elastomer sensor with high dielectric constant and capacitive strain sensing properties by designing polar-nonpolar fluorosilicone multiblock copolymers and introducing poly(dopamine) modified CNTs. (15th October 2021) - Liu, Xueying; Sun, Haibin; Liu, Suting; Jiang, Yingjie; Yin, Zhengming; Yu, Bing; Ning, Nanying; Tian, Ming; Zhang, Liqun
Abstract: The application of silicone rubber as dielectric elastomer sensor is limited by its poor strain sensing performance because of low dielectric constant (ε′). In this study, we designed and fabricated a fluorosilicone dielectric composite with high ε′ and capacitive strain sensing performance by designing polar-nonpolar multiblock fluorosilicone copolymer and introducing poly(dopamine)-modified nanotubes (CNT-PDA). Firstly, a polar (bis(3-aminopropyl)-terminated poly(3, 3, 3-trifluoropropyl) methylsiloxane (H2 N-PFMS-NH2 )) and a nonpolar (bis(3-aminopropyl)-terminated poly(dimethylsiloxane) (H2 N-PDMS-NH2 )) silicone oligomers were synthesized by anionic ring opening polymerization. Then, a series of PFMS/PDMS multiblock copolymer were synthesized through a one-pot polycondensation reaction between isocyanate groups from methylene-bis(4-cyclohexylisocyanate) and amino groups from the as prepared H2 N-PFMS-NH2 and H2 N-PDMS-NH2 . The hydrogen bonds between urea groups act as physical crosslinking points on the multiblock copolymer. The H2 N-PFMS-NH2 chains with polar CF3 groups contribute to high dipole polarizability and thus a high ε'. A strong interfacial adhesion between CNT-PDA and the multiblock copolymer was obtained by hydrogen bonding between the urea groups of the multiblock copolymer and CNT-PDA, resulting in strong interfacial polarizability. The as-prepared composite exhibits a ε′ of about 86.7 at 10 3 Hz and a capacitance change (ΔC) of about 0.91 nF at 200% strain at only 0.3 vol% of CNT-PDA, which was increased by 23.8 and 8.1 times, respectively, compared with the CNT-PDA/commercial nonpolar reference SiR composites. The largely improved ε′ and capacitive strain sensing properties are mainly attributed to the synergistic polarization effect, which was discussed based on impedance analysis and calculating the contribution of each composition on ε' and ΔC. Graphical abstract: Image 1 Highlights: A new polar-nonpolar multiblock fluorosilicone was designed and prepared. A strong interfacial polarizability between CNT-PDA and DE was obtained. CNT-PDA/fluorosilicone composites can be used as DES. Both dielectric constant and sensitivity of DES were largely improved. The relationship between structure and sensitivity was revealed.